2012
DOI: 10.1002/job.1852
|View full text |Cite
|
Sign up to set email alerts
|

Abusive supervision and feedback avoidance: The mediating role of emotional exhaustion

Abstract: Summary The occurrence of abusive supervision is steadily rising. Extant literature continues to expand the number of destructive consequences linked to such improper workplace behavior. This study tested a model linking abusive supervision to feedback avoidance through emotional exhaustion. We invoked conservation of resources theory in our examination of the role that the loss of valued resources plays in instances where abuse is perceived. Results from three rounds of matched data from 460 nurses and 220 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
227
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(265 citation statements)
references
References 44 publications
12
227
0
5
Order By: Relevance
“…Moreover, our research also revealed that OC significantly mediates the relationship between AS and OCB. This was consistent with the work of Wayne et al (2008) [39], Whitman et al (2014) [40], Zhang & Bednall (2016) [44] and Evans et al (2010) [9].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, our research also revealed that OC significantly mediates the relationship between AS and OCB. This was consistent with the work of Wayne et al (2008) [39], Whitman et al (2014) [40], Zhang & Bednall (2016) [44] and Evans et al (2010) [9].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings also confirmed that as the level of AS would increase, the level of PCV in the minds of employees will also increase. Furthermore, results of our research also supported the work of Wayne et al (2008) [39], Whitman et al (2014) [40], Zhang & Bednall (2016) [44] and Zellars et al (2002) [43] who highlighted a positive influence of AS on OC. Our research also affirmed that as the level of AS increases, the level of OC among employees increase.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Above mentioned studies show that the consequences of abusive supervision are significant because it may result the employees to behave counterproductive. The previous studies revealed thatreceiving abuse at work from the supervisor is detrimental to employees' physical and mental health (Tepper2000; Marie Mitchell & Ambrose 2012).The abusive supervision is considered costly to the organizations as it results to an increase inturnover (Tepper, 2006).Abuse may pose threat to the employee and make him insecure.To deal with this insecurity employee adopts certain behavior such as to quit the job (Tepper, 2002;Tepper, 2006)feedback avoidance (Whitman & Oscar Holmes, 2014). Hence, the result shows that the values of first hypothesis are significant and accepted.…”
Section: Note a N = 249b Ab= Abusive Supervision C Ti= Turnover Imentioning
confidence: 91%